Anti‐cytokine autoantibodies suggest pathogenetic links with autoimmune regulator deficiency in humans and mice. (4th February 2013) - Kärner, J.; Meager, A.; Laan, M.; Maslovskaja, J.; Pihlap, M.; Remm, A.; Juronen, E.; Wolff, A. S. B.; Husebye, E. S.; Podkrajšek, K. T.; Bratanic, N.; Battelino, T.; et al.
Summary Autoimmune polyendocrinopathy candidiasis ectodermal dystrophy (APECED) is a recessive disorder resulting from mutations in the autoimmune regulator (AIRE). The patients' autoantibodies recognize not only multiple organ‐specific targets, but also many type I interferons (IFNs) and most T helper type 17 (Th17) cell‐associated cytokines, whose biological actions they neutralize in vitro. These anti‐cytokine autoantibodies are highly disease‐specific: otherwise, they have been found only in patients with thymomas, tumours of thymic epithelial cells that fail to express AIRE. Moreover, autoantibodies against Th17 cell‐associated cytokines correlate with chronic mucocutaneous candidiasis in both syndromes. Here, we demonstrate that the immunoglobulin (Ig)Gs but not the IgAs in APECED sera are responsible for neutralizing IFN‐ω, IFN‐α2a, interleukin (IL)‐17A and IL‐22. Their dominant subclasses proved to be IgG1 and, surprisingly, IgG4 without IgE, possibly implicating regulatory T cell responses and/or epithelia in their initiation in these AIRE‐deficiency states. The epitopes on IL‐22 and IFN‐α2a appeared mainly conformational. We also found mainly IgG1 neutralizing autoantibodies to IL‐17A in aged AIRE‐deficient BALB/c mice – the first report of any target shared by these human and murine AIRE‐deficiency states. We conclude that autoimmunization against cytokines in AIRE deficiency is not simply a mere side effect of chronic mucosal Candida infection, but appears to be related more closely to disease initiation.